O diário artístico digital na formação do artista plástico - Vásquez, Gabriela Cruz (2017)
The theme of this research is the teaching of art. It proposes new ways of intersection between Education, Art and Research, through the, use of digital supports as means of artistic expression. The research made with the participation of two countries in Latin America, Brazil and Mexico, which have an enormous tradition in educational research and artistic production. The idea of this thesis was born and developed in a university in the southeast of Brazil, while the subjects that participated in the data collection were from a university in northern Mexico. The research was covered with, the Partnerships Program for Education and Training (PAEC) in the field of the Cooperation agreement with the Organization of American States (OAS) and the Coimbra Group of Brazilian Universities (CGBU). The research described and analyzed the capacities of an educational and artistic instrument, designed and named in this thesis as the digital artistic diary, with the aim of investigating their capacities in the formation of the plastic artist in the university context.